Enjoyment, Exploration and Education: Understanding the Consumption of Pornography among Young Men with Non-Exclusive Sexual Orientations. (October 2017) - McCormack, Mark; Wignall, Liam
This qualitative research examines the influence of pornography consumption on young men with non-exclusive sexual orientations. Drawing on 35 in-depth interviews with young men from an elite university in the north-eastern United States, we examine how pornography was experienced as a leisure activity to be consumed in free time. Rather than focusing on the potential harms of pornography, we use an inductive analytic approach to explore the broader range of experiences that participants had, since the time they first consumed pornography. We demonstrate that pornography had educational benefits for these young men, related to their sexual desires, emerging sexual identities and for developing new sexual techniques. This study is part of a growing body of research that seeks to develop a holistic understanding of pornography in society, addressing the absence of the lived experience of the consumer in most pornography research.